(untitled) (MAUSAM, 1952)
The note gives the results of an analysis of the rainfall recorded in fifteen minute periods at Madras from the records of the Casella siphon raingauge during the years 1932 to 1947. There is rain in Madras both during the southwest monsoon from June to September and during the northeast monsoon from October to January. During the former season, on many of the rainy days there 18 only a single spell of rainfall and there are very few days when rainfalls more than thrice. The spells are generally of short duration.-less than an hour The rainfall is of low intensity, under 25 cents per hour, Mostly, and there are very few occasion when the intensity exceeds100 cents per hour. Such heavy rains as do occur have a tendency to do so after about 1500 IST and during the night. The maximum intensity of rainfall during rainy days is also generally attained during these hours. During the northeast monsoon, on a number of days rain occurs more than once. The spells are generally of short duration through a few of them may extend over several hours. The rainfall is of low intensity, but heavy rains occur more frequently than during the period of the southwest monsoon. Heavy rains have a tendency to occur after midnight and before early afternoon.